Pengaruh Persepsi Harga, Lokasi, dan Promosi Terhadap Keputusan Pembelian di Kopi Nako Bogor - Kavita Syaidina Muflihah; Jamaludin Khalid (CV. Ulil Albab Corp, 2024)
The purpose of this research it to evaluate the impact of price, location and promotion perceptions on purchasing decisions. This research focuses on the population of customer who come to Kopi Nako Bogor by distributing questionnaires to customers who have made purchase at Kopi Nako Bogor at least twic, totalling 100 customers taken as respondents in this research. Linear regression analysis using SPSS application was used to assess the relationship between the variables being considered. The research result show taht while perceptions of price, location, promotions have a significant impact on purchasing decisions. This research can provide valuable contributions and useful evalutions for Kopi Nako Bogor to improve policy considerations and formulate effective marketing strategies to achive predetermined sales targets.